2021
DOI: 10.1177/0897190021997032
|View full text |Cite
|
Sign up to set email alerts
|

Medication Therapy Management for Texas MediCAID Patients With Asthma and Chronic Obstructive Pulmonary Disease—A Pilot Study

Abstract: Background: Pharmacists can play an important role in providing medication therapy management (MTM) services, which focus on appropriate medication use. This pilot study aimed to describe pharmacists’ MTM service provision, results/outcomes of pharmacists’ recommendations and resolution/acceptance rate among patients with high-risk asthma and/or chronic obstructive pulmonary disease (COPD). Methods: This was a prospective descriptive study of MTM services provided by community pharmacists to Texas Medicaid pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“… 39 Healthcare providers including pharmacists may identify rescue inhaler overuse and resolve MRPs, while monitoring patients with ACO. 40 Our study also showed that the oral corticosteroid fill claims decreased during the first few months of 2020, which may have been a result of preventive measures such as the facemask use and social distancing policies. 41 …”
Section: Discussionsupporting
confidence: 54%
“… 39 Healthcare providers including pharmacists may identify rescue inhaler overuse and resolve MRPs, while monitoring patients with ACO. 40 Our study also showed that the oral corticosteroid fill claims decreased during the first few months of 2020, which may have been a result of preventive measures such as the facemask use and social distancing policies. 41 …”
Section: Discussionsupporting
confidence: 54%
“…adverse drug reactions (ADRs) identified through MTM consultations pertain to medication appropriateness, efficacy, safety, and adherence [4]. To provide additional insight, a study carried out in 2021 uncovered 192 Medication-related Problems (MDRs) during MTM interventions for a sample of 384 individuals with type 2 diabetes, hypertension, and similar coexisting health conditions [5]. Notably, this study observed a notable increase in health promotion, particularly within the diabetic subgroup [5].…”
Section: Introductionmentioning
confidence: 95%
“…To provide additional insight, a study carried out in 2021 uncovered 192 Medication-related Problems (MDRs) during MTM interventions for a sample of 384 individuals with type 2 diabetes, hypertension, and similar coexisting health conditions [5]. Notably, this study observed a notable increase in health promotion, particularly within the diabetic subgroup [5]. An additional study, which highlighted the beneficial impacts of MTM services, examined 63 patients dealing with asthma and chronic obstructive pulmonary disease, with the majority of cases involving complex medication regimens (53.2%).…”
Section: Introductionmentioning
confidence: 99%